1989
DOI: 10.1152/ajpheart.1989.257.2.h444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen deprivation on metabolism of arachidonic acid by cultures of rat heart cells

Abstract: To investigate the mechanisms responsible for the impairment of phospholipid metabolism observed in ischemic cells, we have studied the effect of conditions simulating ischemia on the metabolism of arachidonic acid (AA) by muscle (M-) and nonmuscle (F-) cells isolated from newborn rat hearts and cultured separately. In muscle cells, oxygen deprivation induces a significant stimulation of the release of [14C]AA from prelabeled cells associated with a preferential redistribution of [14C]AA into cell triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Oxygen deprivation and hydrodynamic shear stress have been shown to increase membrane phsopholipid metabolism (Freyss-Beguin, et al 1989;Nollert et al, 1989Nollert et al, ,1991Bhat and Block, 1992;Michiels et aZ., 1993). In both cases there was a significant increase in prostaglandin synthesis, since the cell models chosen have a disposition for the production of prostaglandins in response to cell stress.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen deprivation and hydrodynamic shear stress have been shown to increase membrane phsopholipid metabolism (Freyss-Beguin, et al 1989;Nollert et al, 1989Nollert et al, ,1991Bhat and Block, 1992;Michiels et aZ., 1993). In both cases there was a significant increase in prostaglandin synthesis, since the cell models chosen have a disposition for the production of prostaglandins in response to cell stress.…”
Section: Discussionmentioning
confidence: 99%
“…Radiolabelled fatty acids and phospholipids were extracted by a modified Folch method, separated by thin layer chromatography using Silica Gel 60A plates with a mobile phase of chloroform-methanol and distilled water (65/25/4, v/v), then localized with a Berthold scanner and quantified by liquid scintillation [29]. Analysis of the incubation buffer indicated that 1 95% of the released radioactivity was in the form of free arachidonic acid.…”
Section: Quantification Of Arachidonic Acid Release In Huvecmentioning
confidence: 99%
“…In contrast, in aortic regurgitation or intrarenal aortic stenosis, conditions in which Ang II and aldosterone levels are normal, cardiac hypertrophy is not accompanied by elevated collagen concentrations (25,26). It has been reported that angiotensin converting enzyme inhibitor prevents DNA synthesis in interstitial cells after myocardial infarction and myocardial fibrosis ( 13,27 (29) were used as positive controls for the primary antibodies. The following primary antibodies were tested: a polyclonal antibody against von Willebrand factor (DAKOPATTS, Copenhagen, Denmark) for the detection ofendothelial cells, a monoclonal antibody against sarcomeric tropomyosin (Sigma Immunochemicals) for cardiomyocytes, a monoclonal antibody against smooth muscle myosin heavy chain (Sigma Immunochemicals) for vascular smooth muscle cells, and a monoclonal antibody against vimentin (Sigma Immunochemicals).…”
Section: Introductionmentioning
confidence: 99%